2018
DOI: 10.1111/joor.12603
|View full text |Cite
|
Sign up to set email alerts
|

Bite or brain: Implication of sensorimotor regulation and neuroplasticity in oral rehabilitation procedures

Abstract: Tooth loss, decreased mass and strength of the masticatory muscles leading to difficulty in chewing have been suggested as important determinants of eating and nutrition in the elderly. To compensate for the loss of teeth, in particular, a majority of the elderly rely on dental prosthesis for chewing. Chewing function is indeed an important aspect of oral health, and therefore, oral rehabilitation procedures should aim to restore or maintain adequate function. However, even if the possibilities to anatomically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 144 publications
(398 reference statements)
7
75
0
1
Order By: Relevance
“…Animal research has confirmed that occlusal changes can induce neuroplasticity in the motor cortex, and fMRI studies have consistently shown that functional changes in the sensorimotor cortex reflect not just individual differences but also continuous adaptation over time . It should be noted, however, that most of the studies included in the current meta‐analysis were observational and cross‐sectional studies, the results of which cannot be interpreted as effects of the neuroplasticity of oral sensorimotor rehabilitation . Nevertheless, our findings demonstrate considerable consistency in the identification of brain loci, providing novel evidence of the reliability of fMRI‐based investigations in determining the brain representation of orofacial sensorimotor functions.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Animal research has confirmed that occlusal changes can induce neuroplasticity in the motor cortex, and fMRI studies have consistently shown that functional changes in the sensorimotor cortex reflect not just individual differences but also continuous adaptation over time . It should be noted, however, that most of the studies included in the current meta‐analysis were observational and cross‐sectional studies, the results of which cannot be interpreted as effects of the neuroplasticity of oral sensorimotor rehabilitation . Nevertheless, our findings demonstrate considerable consistency in the identification of brain loci, providing novel evidence of the reliability of fMRI‐based investigations in determining the brain representation of orofacial sensorimotor functions.…”
Section: Discussionsupporting
confidence: 68%
“…First, as stated above, though these activated loci do not represent the effects of neuroplasticity per se , they may represent functional markers primarily related to teeth occlusion and may thus be potential sites at which to examine the neuroplastic effects of oral rehabilitation or to find potential targets for further intervention (eg for TMS). Second, one of the major challenges in prosthodontic treatment is the existence of individual differences in sensorimotor adaptation, which leads to great variation in treatment outcome . Recent studies have revealed that individual functional and structural variations in the sensory and motor areas may predict individual differences in masticatory performance .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that masticatory performance in the edentulous elderly may be also associated with physical performance parameters, which are significant predictors of decreased activities of daily living . Hence, a relevant impact of ageing on masticatory function is expected due to the progressive impairment on overall physical capacity, which is frequently accompanied by a decrease in body weight and muscle mass, leading to frailty and associated morbidity in the elderly …”
Section: Discussionmentioning
confidence: 99%
“…These brainstem and higher centre neurons and indeed the behaviours to which they contribute can be regulated by modulatory influences from several brainstem and higher CNS centres, examples of which are shown in Figure . These influences involve the release of several inhibitory and excitatory chemical mediators that act upon receptor processes (eg, glutamatergic, gamma‐amino butyric acid [GABA], opioid) in non‐neural cells (eg, glia) as well as neurons in the TBSNC, STN and cranial nerve motor nuclei (eg, trigeminal motor nucleus) and adjacent interneuronal sites (for review, see refs).…”
Section: Regulation Of Oro‐facial Sensorimotor Functionsmentioning
confidence: 99%